Efficiently Unequal: The Global Rise of Kaldor-Hicks Neoliberalism - Cook, Eli (Global intellectual history (Abingdon, England), 2024)
This paper offers a history of the 'Kaldor-Hicks' concept of economic efficiency from its European birth in the 1930s to its American resurgence in the 1970s to its widespread implementation in the Global South by the early twenty-first century. While philosophers, economists and legal theorists have written widely about Kaldor-Hicks - global-minded intellectual historians have not. As a result, scholars have yet to place its creation, dissemination and ascendency into a broader historical context or examine the reasons behind its global spread. As this paper will demonstrate through the rise of cost-benefit analyses based on 'willingness to pay' metrics, while Kaldor-Hicks efficiency was invented by neoclassical economists in the late 1930s, its ascent to policy dominance is part-and-parcel of the neoliberal revolution of the past half century. Linking the history of economic thought with the rise of global neoliberalism, this paper demonstrates how Kaldor-Hicks efficiency emerged as a central pillar of a new, interventionist, wealth-maximizing and market-based form of depoliticized technocratic governance that not only marginalizes distributive concerns but actively exacerbates the problem of global inequality.